A Multilevel Examination of Risk/Need Change Scores, Community Context, and Successful Reentry of Committed Juvenile Offenders. (January 2017) - Baglivio, Michael T.; Wolff, Kevin T.; Jackowski, Katherine; Greenwald, Mark A.
Current theory and practice dictates the use of risk/needs assessment to guide programming to reduce reoffending. Limited research has examined assessment change scores and recidivism, none examining whether such changes moderate the effects of deleterious community contexts. We examine a multiyear statewide sample of juvenile offenders returning to the community from residential placement ( N = 12, 302). We address whether changes in dynamic risk/needs scores predict official recidivism upon return, community socioeconomic contexts predict recidivism, and which risk/needs changes moderate the effects of context. Findings reveal 6 of the 17 change scores affect reoffending, context matters, and some change scores moderate contextual effects.